Borges the Unacknowledged Medievalist - Toswell, M. author. aut Link
XVI, 109 p.
Keywords: The Argentinian writer and poet Jorge Luis Borges (1899-1986) was many things during his life, but what has gone largely unnoticed is that he was a medievalist, and his interest in Germanic medievalism was pervasive throughout his work. This study will consider the medieval elements in Borges creative work and shed new light on his poetry.